Estudio del equilibrio higroscopico de Phaseolus vulgaris L. en relacion a diferentes niveles de humedad - Álvarez S, E. (International Center for Tropical Agriculture, 1976)
In hot, humid areas some 40 percent of stored grain in lost; however, control of RH generally requires expensive equipment. The objectives of this expt were to evaluate the behavior of bean seeds of different size, color and moisture content at different levels of RH and to correlate adsorption and desorption to show the effect of hysteresis. Half the lot of seeds was soaked in water. the rest, oven dried at 33 degrees Celsius for 6 h. They were stored in aluminum foil bags and placed in sealed metal boxes containing different concentrations of glycerin. The dry seeds behaved hygroscopically, moisture content increasing with increases in RH. The same was true for the soaked seeds, possibly due to the low hygroscopic capacity of the glycerin. (CIAT)